Exploring novel cancer-associated fibroblast markers of colorectal tumour microenvironment in differentiating the mechanisms of right-sided and left-sided colorectal cancer - Zawawi, Sahira Syamimi Ahmad (2025)
Colorectal cancer (CRC) is a heterogeneous disease, often classified into right-sided CRC (RCRC) and left-sided CRC (LCRC), which differ in many ways, including their histological and molecular phenotypes. Tumour environment (TME) of the colon and cancer-associated fibroblasts (CAFs), the main cellular component of TME have been described to drive CRC progression. Accumulation of CAF reflect poor prognosis in CRC. Due to its vital role, CAFs are being studied as a prime target for cancer therapy. In contrast to previous reports in which RCRC and LCRC were classified based on the epithelial cancer cell mutational profiles or histology, CAFs influence in differentiating mechanism of these two CRC entities has yet to be discovered. This study aimed to explore novel CAF markers of colorectal TME in differentiating the mechanisms of RCRC and LCRC. CAFs derived from CRC and non-activated fibroblasts (NFs) derived from adjacent normal colon tissues were established. For fibroblast phenotypic characterisation, immunofluorescence (IF) staining of amine oxidase copper containing 3 (AOC3), leucine-rich repeat-containing 17 (LRRC17), and alpha smooth muscle actin (α-SMA) were performed and the fibroblasts morphology was recorded. The contractile and proliferation phenotype of the fibroblasts were compared through collagen contraction and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assays. Their gene profiles were analysed via microarray analysis (Clariom S (Human) assay) to screen differentially expressed genes (DEGs). Epithelial marker, epithelial cellular adhesion molecule (EpCAM) was included. Epithelial cell lines of CRC (SW620) and cervical cancer (C33A) were incorporated as controls. Fibroblasts treated with TGFβ (10ng/ml) showed significant AOC3 downregulation, LRRC17, and α-SMA upregulation, along with increased contractility, compared to serum free medium (p<0.05). Conditioned medium (CM) derived from fibroblasts promoted SW620 cells proliferation. CAFs from RCRC (RC) denote prominent inflammatory phenotype with chemokines-rich markers expression whereas, CAFs from LCRC (LC) demonstrate myofibroblastic CAFs (myoCAFs) phenotype with myoCAF markers expression. RNA-binding protein with multiple splicing (RBPMS) expression was significantly upregulated in fibroblasts, with distinct patterns of expression between fibroblasts from different colon sidedness as indicated by microarray (p<0.05), and validated via western blot. Additionally, TGFβ1 promoted RBPMS expression in LC but suppressed RBPMS expression in RC. This is the first study to explore the role of CAFs in CRC based on the colon sidedness. The regulation of RBPMS expression in CAFs by TGFβ elucidate the different mechanisms of RCRC and LCRC. In conclusion, RBPMS could serve as a novel CAFs marker for targeted approach against CRC based on its sidedness.